Studies on the Use of Spectrum Sharing for Mobile Network Operator in Indonesia - Hafiza, Lia; Wahyuningrum, Reni Dyah; Yudiansyah, Yudiansyah (Journal of Informatics and Communication Technology (JICT), 2023)
Since telecom businesses have already reached their peak level of revenue, their future is expected to get worse. To save as much money as possible, greater than sixty percent of mobile network operators (MNO) in the worldwide implemented Radio Access Network-Sharing or RAN-Sharing. Earnings before interest, taxes, depreciation, and amortization (EBITDA) pressure and the limited availability of the frequency spectrum are two factors that propel. Spectrum sharing can be one solution to reduce Capital Expenditure and Operational Expenditure operator costs, address spectrum shortages and promote development across the region in Indonesia. With different coverage of underserved areas, the number of assets in the form of BTS and license of frequency spectrum usage are owned by each operator. Research on business impacts for operators needs to be assessed to be able to determine business strategy.